Frequency of Common Eye Diseases in Pediatric Outpatient Department of A Tertiary Care Hospital - Arshad Shaikh, Kaneez Fatima, Erum Shahid (Pakistan Journal of Ophthalmology, 2015)
Purpose: To determine the frequency of common eye diseases in children attending outpatient department of a tertiary care hospital. Material and Methods: A total of 186 patients with complaints of reduced vision, redness, itching and watering of eyes were included in this study. Detailed examination was done at Department of Ophthalmology, Abbasi Shaheed Hospital, Karachi. Six months from 1st August 2013 to 31st January 2014. Refraction was performed under cycloplegia. Anterior segment was examined with the help of direct ophthalmoscope and slit lamp. Posterior segment examination was performed after dilating pupil with mydriatic drops using direct and indirect ophthalmoscopes. Intraocular pressure was checked where needed. All information was entered in proforma. Data was analyzed on SPSS 10. Mean and standard deviation were computed for age. Frequency and percentages were computed for categorical variables like conjunctivitis, vernal keratoconjunctivitis, nasolacrimal duct blockage, hypermetropia and myopia. Results: Frequency of commonest eye disease was conjunctivitis i.e. 41.3% followed by nasolacrimal duct blockage 25.8%, vernal keratoconjunctivitis 16.1%, hypermetropia 9.1% and myopia 7.5%. Conclusion: The most common eye problem was conjunctivitis. Nasolacrimal duct blockage presented the second most common cause of pediatric ophthalmic disorder. Males were more affected than females. Key Words: Eye diseases, conjunctivitis, nasolacrimal, keratoconjunctivitis.